Peran Keluarga dalam Memenuhi Hak-Hak Anak Fatherless Menurut Hukum Islam dan UU No. 35 Tahun 2014 Tentang Perlindungan Anak (Studi Kasus Desa Mojoduwur Kecamatan Mojowarno Kabupaten Jombang) - Dava Nadila Amalia; Mochammad Fahd Akbar (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The presence and role of a father play a significant role in a child's development. However, under certain circumstances, such as divorce or emotional strain, children can experience fatherlessness, potentially impacting the fulfillment of their rights. This study aims to analyze the fulfillment of the rights of fatherless children by families in Mojoduwur Village, Mojowarno District, Jombang Regency, from the perspective of Islamic law and positive law. This study used empirical legal research methods, collecting data through interviews and direct observation of the community's social conditions. The results indicate that, from an Islamic legal perspective, the family still plays a significant role in fulfilling the rights of fatherless children. However, in the practice of positive law, some parents have been found to neglect their obligations after divorce by handing over the care of their children to their grandmothers on an ongoing basis without adequate responsibility. This situation has the potential to lead to child neglect if it is not accompanied by the fulfillment of obligations by the biological parents. Although the child's needs can be met by the family, legal responsibility remains with the parents and cannot be transferred to another party. This study emphasizes the importance of legal awareness and moral responsibility of parents in ensuring the fulfillment of children's rights after divorce.